Mindfulness and headache: A "new" old treatment, with new findings. (October 2016) - Andrasik, Frank; Grazzi, Licia; D'Amico, Domenico; Sansone, Emanuela; Leonardi, Matilde; Raggi, Alberto; Salgado-García, Francisco
Background: Mindfulness refers to a host of procedures that have been practiced for centuries, but only recently have begun to be applied to varied pain conditions, with the most recent being headache. Methods: We reviewed research that incorporated components of mindfulness for treating pain, with a more in depth focus on headache disorders. We also examined literature that has closely studied potential physiological processes in the brain that might mediate the effects of mindfulness. We report as well preliminary findings of our ongoing trial comparing mindfulness alone to pharmacological treatment alone for treating chronic migraine accompanied by medication overuse. Results: Although research remains in its infancy, the initial findings support the utility of varied mindfulness approaches for enhancing usual care for headache management. Our preliminary findings suggest mindfulness by itself may produce effects comparable to that of medication alone for patients with chronic migraine and medication overuse. Conclusions: Much work remains to more fully document the role and long term value of mindfulness for specific headache types. Areas in need of further investigation are discussed.